Assessing Ontario's Personal Support Worker Registry - Audrey Laporte; David Rudoler (McMaster University Library Press, 2013)
In response to the growing role of personal support workers (PSWs) in the delivery of health care services to Ontarians, the Ontario government has moved forward with the creation of a PSW registry. This registry will be mandatory for all PSWs employed by publicly funded health care employers, and has the stated objectives of better highlighting the work that PSWs do in Ontario, providing a platform for PSWs and employers to more easily access the labour market, and to provide government with information for human resources planning. In this paper we consider the factors that brought the creation of a PSW registry onto the Ontario government's policy agenda, discuss how the registry is being implemented, and provide an analysis of the strengths and weaknesses of this policy change.